1983
DOI: 10.1093/ije/12.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Prevention of Coronary Heart Disease in Women: The Finnish Mental Hospital Study

Abstract: A controlled intervention trial, with the purpose of testing the hypothesis that the incidence of coronary heart disease (CHD) could be decreased by the use of a serum-cholesterol-lowering (SCL) diet, was carried out in two mental hospitals near Helsinki in 1959-71. The subjects were hospitalized middle-aged women. One of the hospitals received the SCL diet, ie a diet low in saturated fats and cholesterol and relatively high in poly-unsaturated fats, while the other served as the control with a normal hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
5

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 0 publications
0
61
0
5
Order By: Relevance
“…66 Of the remaining 4 studies, 1 reported a significant 45% reduction in risk, 59 whereas no significant effect was seen in the others. 60,61,65 These trials tested the effect of replacing saturated fatty acids; no randomized trial has reported the effects of replacing carbohydrate or protein with omega-6 PUFAs on CHD risk. Although limitations are present for each trial, the combined results of these studies and the observational trials provide evidence that replacing saturated fatty acid or refined carbohydrate (eg, sugars, white bread, white rice, potatoes) with omega-6 PUFAs reduces CHD risk.…”
Section: Omega-6 Pufa Consumption and Chd Events: Randomized Controllmentioning
confidence: 99%
“…66 Of the remaining 4 studies, 1 reported a significant 45% reduction in risk, 59 whereas no significant effect was seen in the others. 60,61,65 These trials tested the effect of replacing saturated fatty acids; no randomized trial has reported the effects of replacing carbohydrate or protein with omega-6 PUFAs on CHD risk. Although limitations are present for each trial, the combined results of these studies and the observational trials provide evidence that replacing saturated fatty acid or refined carbohydrate (eg, sugars, white bread, white rice, potatoes) with omega-6 PUFAs reduces CHD risk.…”
Section: Omega-6 Pufa Consumption and Chd Events: Randomized Controllmentioning
confidence: 99%
“…On the other hand, Hooper et al excluded the big Helsinki Mental Hospital Trial which was a large crossover trial in two long-stay hospitals (Turpeinen et al, 1979;Miettinen et al, 1983). First one, then after 7 y the other hospital implemented a reduced saturated, increased polyunsaturated fat diet across the institution, while the other hospital served the standard Finnish diet of the 1960s.…”
Section: Omission Of a Major Trialmentioning
confidence: 99%
“…Both saturated and trans fatty acids has been shown to increase the risk of cardiovascular diseases [3][4][5][6]. In contrast, unsaturated fatty acids have been shown to have a potentially therapeutic benefit for patients with type-2 diabetes [7], dementia [8], cystic fibrosis [9], and arguably to reduce the risk of coronary heart diseases [10][11][12][13]. In particular, polyunsaturated fatty acids (PUFAs) such as α-linolenic acid (omega-3) and linoleic acid (omega-6) have received the most attention as humans cannot synthesize either of these molecules.…”
Section: Introductionmentioning
confidence: 99%